THE IDENTITY ISSUE IN OKINAWAN LITERATURE OF THE 20TH CENTURY (ON THE EXAMPLE OF THE SHORT STORIES OFFICER UKUMA IKEMIYAGI SEKIHŌ AND MOTHERS, WOMEN NAKANDAKARI HATSU). - Spinek-Bomke, Anna (Porównania, 2016)
The aim of this article is to analyse the feeling of national identity of the Ryukyuans and the way in which this problem is presented in selected Okinawan prose: short stories Officer Ukuma by Ikemiyagi Sekiho and Mothers, Women by Nakandakari Hatsu. Inhabitants of Ryukyu Kingdom, incorporated by Japan only in 1879, were both culturally and ethnically different from the Japanese. Problems originating from their double, Japanese-Okinawan identity are presented in the first of the stories. The main topic of Mothers, Women, written fifty years later, are traumatic wartime memories of the heroines and their influence on both the Okinawans’ everyday life and their attitude towards the inhabitants of Japan proper (hondo).